2016
DOI: 10.1136/archdischild-2015-309731
|View full text |Cite
|
Sign up to set email alerts
|

The use, appropriateness and outcomes of outpatient parenteral antimicrobial therapy

Abstract: Objective Outpatient parenteral antimicrobial therapy (OPAT) is increasingly used to treat children at home, but studies in children are scarce. We aimed to describe the use, appropriateness and outcomes of OPAT in children. Design This was a 12-month prospective observational study. Setting The hospital-in-the-home programme of The Royal Children's Hospital Melbourne. Patients All patients receiving OPAT. Interventions Data were collected including demographics, diagnosis, type of venous access and antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
65
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 21 publications
(25 reference statements)
4
65
1
Order By: Relevance
“…Clinicians often fail to provide adequate patient oversight7; Hodgson et al identified that 26% of their paediatric OPAT patients received an incorrect dose, route or duration of antibiotics and an inappropriate indication for treatment was cited in 6% 8. Overall, drug-related and line-related complications are reported to occur in 20% to 30% of paediatric OPAT patients, correlating with increasing intravenous therapy durations 4 9–12…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians often fail to provide adequate patient oversight7; Hodgson et al identified that 26% of their paediatric OPAT patients received an incorrect dose, route or duration of antibiotics and an inappropriate indication for treatment was cited in 6% 8. Overall, drug-related and line-related complications are reported to occur in 20% to 30% of paediatric OPAT patients, correlating with increasing intravenous therapy durations 4 9–12…”
Section: Introductionmentioning
confidence: 99%
“…Hodgson et al 3 describe a large prospective cohort of children managed within an OPAT service in Australia. They attempted to both quantify their workload and assess the appropriateness of their IVAB prescribing.…”
mentioning
confidence: 99%
“…The convenience of OPAT makes it extremely easy to administer long courses of IVABs. Due to the paucity of high-quality evidence available to inform decision making about antibiotic prescribing, including the optimal route and duration of administration, Hodgeson et al 3 have been forced to resort to expert opinion to decide whether prescribing was appropriate or not within their cohort of patients. In their opinion, 8% of IVAB courses were too long and 6% too broad, though infectious diseases specialists are often more likely to err on the side of caution and prescribe longer courses of antibiotics than other doctors 4.…”
mentioning
confidence: 99%
See 2 more Smart Citations